V.3 - "Vora, Rajendra (ed.)" (New Delhi, 2002)
One of the major objectives of Lal Bahadur Shastri National Academy of Administration, Mussoorie, which imparts training to Indian Administrative Service (IAS) officers, is not only to sensitize them towards the plight of rural people, but also to equip them with an in-depth understanding of rural issues. The IAS officer trainees are required to prepare a village study report as a part of their district assignments after conducting extensive questionnaire-based household survey.This four-volume series of Socio-Economic Profile of Rural India is based on the village study reports of IAS trainees. Volume one on South India, published in the year 2002, contains papers of the States of Andhra Pradesh, Karnataka, Kerala and Tamil Nadu. Volume two on North-East India, published in the year 2004, covers the states of Assam, Manipur, Tripura and Nagaland.The present volume on North-Central and Western India, having study reports of the States of Himachal Pradesh, Punjab, Haryana, Gujarat and Maharashtra, addresses issues like demographic features, socio-cultural aspects, health, gender inequality, agrarian relationship, land reforms, occupational pattern, poverty and local government. The last volume (Vol. IV), pertaining to Eastern India (Bihar, Orissa, Uttar Pradesh and West Bengal) is in the pipeline.
Keywords: India - Social conditions